Assessment of environmental factor effects on fatigue and healing performance of asphalt mixtures - Aljubory, Ahmed Ibrahim Ahmed (2019)
Oxidative ageing and moisture damage can be an example of time-dependent environmental conditions affecting the durability of bituminous mixtures simultaneously. Ageing may excessively increase the stiffness modulus and moisture damage may excessively decrease it causing different types of distresses such as cracking and rutting. Consequently, this thesis set out to investigate and understand the individual and combined effects of moisture damage and/or ageing on fatigue and healing performance of asphalt mixtures.